Excess postexercise oxygen consumption decreases with swimming duration in a labriform fish: Integrating aerobic and anaerobic metabolism across time. Issue 10 (27th September 2019) - Cordero, Gerardo A.; Methling, Caroline; Tirsgaard, Bjørn; Steffensen, John F.; Domenici, Paolo; Svendsen, Jon C.
Abstract: Many vertebrate animals employ anaerobic pathways during high‐speed exercise, even if it imposes an energetic cost during postexercise recovery, expressed as excess postexercise oxygen consumption (EPOC). In ectotherms such a fish, the initial anaerobic contribution to exercise is often substantial. Even so, fish may recover from anaerobic pathways as swimming exercise ensues and aerobic metabolism stabilizes, thus total energetic costs of exercise could depend on swimming duration and subsequent physiological recovery. To test this hypothesis, we examined EPOC in striped surfperch ( Embiotoca lateralis ) that swam at high speeds (3.25 L s −1 ) during randomly ordered 2‐, 5‐, 10‐, and 20‐min exercise periods. We found that EPOC was highest after the 2‐min period (20.9 mg O2 kg −1 ) and lowest after the 20‐min period (13.6 mg O2 kg −1 ), indicating that recovery from anaerobic pathways improved with exercise duration. Remarkably, EPOC for the 2‐min period accounted for 72% of the total O2 consumption, whereas EPOC for the 20‐min period only accounted for 14%. Thus, the data revealed a striking decline in the total cost of transport from 0.772 to 0.226 mg O2 ·kg −1 ·m −1 during 2‐ and 20‐min periods, respectively. Our study is the first to combine anaerobic and aerobic swimming costs to demonstrate an effect of swimming duration on EPOC in fish. Clarifying the dynamic nature of exercise‐related costs is relevant to extrapolating laboratory findings to animals in the wild. Abstract : The total energetic cost of exercise in Striped seaperch (Embiotoca lateralis) as estimated by the sum of oxygen consumption during exercise (black bar plot) and excess post exercise oxygen consumption (EPOC; area under curve). Research Highlight: Many animal species employ anaerobic pathways during exercise, though this later imposes an energetic cost, that is, excess postexercise oxygen consumption (EPOC). Our study combined anaerobic and aerobic swimming costs to show an effect of swimming duration on fish exercise recovery and EPOC.